Relacion Entre La Densidad Óptima Agronomica Y El Número De Granos Por Planta En Maíz (Zea Maysl.) - Cecilia Cerliani; Gabriel P. Esposito; Federico D. Morla; Guillermo R. Balboa; Rafael A. Naville (European Scientific Journal, ESJ, 2018)
The density of sowing (D) is one of the main management practices that influences the yield (Y) of corn. There exists a density value in which the yield is maximum (OPD), depending on the environment, the genotype and its interaction. The objectives of this project were: i-To determine the OPD for two corn genotypes in different productive environments; ii- Analyze the relationship between the number of kernel fixed per plant (KNP) and its plant growing rate (PGR) to different environments and genotypes iii- Determine the KNP that is related to the OPD for two corn genotypes. Three experiments were carried out in different locations (L) of Córdoba (Argentina) during 2013/14, comparing 2 genotypes (G) in 2 management zones (MZ). The statistical design was random blocks, with a factorial arrangement of subdivided plots, with L, MZ and G being the primary, secondary and tertiary factors, respectively. In addition, 5 D were planted to obtain the relationships that estimate OPD, PGR, KNP and Y. The results indicate that OPD was affected by L; the relationship between PGR and KNP was not modified by the environment, but by G. The PGR coincident with the OPD was modified by the G interaction: L. The OPD the PGR was between 2.74 to 4.81 g d -1 , which were associated with the NGP that varied only between 509 and 603 grains p-1 .